Meta-Analisis Dari Dampak Adopsi Ifrs Pada Analyst Forecast Accuracy - Felix Hertanu Wijaya; Vena Purnamasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
IFRS adoption in various countries has prompted research related to the regulatory changes impact. Different regulations can affect financial information quality. Accounting information function to analysts’ financial statements. The accounting information quality affected by the accounting standards adoption affects the analysts' forecasts. Researchers carried out research related to the IFRS adoption impact. However, we need to see the results of studies consistently to draw general conclusions. The purpose is to answer the IFRS adoption impact in general. The consistency of the results of this study can be proven by conducting a meta-analysis. The results of the heterogeneity test with CMA are 0.107 (p-value), meaning sampling error didn't occur and in the calculation of correlation analysis p-value was 0.353, which means IFRS adoption studies on analyst forecast accuracy were homogeneous. The meta-analysis results show that adopting IFRS has no impact on the accuracy of the analyst's forecasting results. Therefore, the implementation of IFRS which mostly changes the stanard is a policy change. Keywords: Analysts Forecast Accuracy, IFRS, Meta-Analysis